2021
DOI: 10.3390/nu13020470
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Combined Gluten- and Casein-Free Diet on Children and Adolescents with Autism Spectrum Disorders: A Systematic Review and Meta-Analysis

Abstract: There has been a growing interest in the gastrointestinal system and its significance for autism spectrum disorder (ASD), including the significance of adopting a gluten-free and casein-free (GFCF) diet. The objective was to investigate beneficial and safety of a GFCF diet among children with a diagnosis of ASD. We performed a systematic literature search in Medline, Embase, Cinahl, and the Cochrane Library up to January 2020 for existing systematic reviews and individual randomized controlled trials (RCTs). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 43 publications
1
24
0
5
Order By: Relevance
“…This is believed to occur because milk contains the FRα protein which may react immunologically in the gut or cause an increase in cross-reactive FRAAs in the blood. Several types of diets (such as a casein-free diet) which have been reported to show some effectiveness in ASD are milk-free diets [98,99] although this has not been found in some studies [100]. Thus, it is possible that dietary treatments not uncommonly used to treat children with ASD may have a therapeutic effect by lowering the concentration of FRAAs in the blood.…”
Section: Adjunctive Treatments Studied For Fraa Positive Patientsmentioning
confidence: 99%
“…This is believed to occur because milk contains the FRα protein which may react immunologically in the gut or cause an increase in cross-reactive FRAAs in the blood. Several types of diets (such as a casein-free diet) which have been reported to show some effectiveness in ASD are milk-free diets [98,99] although this has not been found in some studies [100]. Thus, it is possible that dietary treatments not uncommonly used to treat children with ASD may have a therapeutic effect by lowering the concentration of FRAAs in the blood.…”
Section: Adjunctive Treatments Studied For Fraa Positive Patientsmentioning
confidence: 99%
“…Diet plays a large role in determining gut microbial composition and function (23,24); thus, a selective diet could affect the gut microbial community. Some parents of children with ASD suspect that food allergies and sensitivity to dietary gluten and casein result in gastrointestinal problems and therefore implement gluten-free, casein-free (GF/CF) diets (25). However, despite the selective eating habits and specialized diets of some individuals on the autism spectrum, such as a GF/CF diet, there is no evidence of differential energy intake and growth compared to neurotypical children (26,27).…”
Section: Asd and The Gutmentioning
confidence: 99%
“…However, despite the selective eating habits and specialized diets of some individuals on the autism spectrum, such as a GF/CF diet, there is no evidence of differential energy intake and growth compared to neurotypical children (26,27). A small number of studies have found changes in ASD-related behaviors following implementation of a GF/CF diet (28), but many other studies have identified no such changes (25,29). Overall, the effect of a GF/CF diet on ASD behaviors remains inconclusive.…”
Section: Asd and The Gutmentioning
confidence: 99%
“…Another systematic review based on the findings of six randomized controlled trials updated the evidence of the therapeutic effectiveness of the GFCF diet in childhood ASD and concluded that there is little evidence supporting beneficial effects of the diet (Piwowarczyk et al, 2018). A recent systematic review and meta-analysis, based on six relevant randomized controlled trials investigating possible benefits of the GFCF diet in children diagnosed with ASD found no effects on clinician-reported autism core symptoms, parent-reported functional level or behavioral difficulties (Keller et al, 2021). The quality of evidence ranged from low to very low due to serious risk of bias, inconsistency and imprecision.…”
Section: Intervention Studies Using the Gfcf Dietmentioning
confidence: 99%